2004
DOI: 10.1063/1.1721027
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of Liquid Cannon Target Driven by Fiber Laser for Micro-Thruster in Satellite

Abstract: We propose a new concept controlling a satellite by a fiber laser loaded in it and demonstrated the acceleration of pendulum with 7kW/2n and 2kHz fiber laser, and measured the Cm of 16Ns/MJ corresponding to the scaling of YAG laser. This laser can be easily bundled to generate much larger power. For more efficient acceleration, we propose "metal-free water cannon target", the new concept of propulsion using only water. The momentum coupling coefficient of 2500[Ns/MJ] was achieved with vacuum pump oil instead o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Although the water is transparent to near infra-red and visible lasers, high intensity laser can induce breakdown ofwater ifthe laser is focused inside the water as in Fig.4. We call this system "metal-free water cannon" [13] and succeeded to gain the thrust comparable to metal target covered by water. The maximum coupling coefficient was 2444.4N.sIMJ, which is comparable to 3536. iN.…”
Section: Laser Driven Automobilementioning
confidence: 99%
“…Although the water is transparent to near infra-red and visible lasers, high intensity laser can induce breakdown ofwater ifthe laser is focused inside the water as in Fig.4. We call this system "metal-free water cannon" [13] and succeeded to gain the thrust comparable to metal target covered by water. The maximum coupling coefficient was 2444.4N.sIMJ, which is comparable to 3536. iN.…”
Section: Laser Driven Automobilementioning
confidence: 99%
“…Remote torque production and tractor-beam-like propulsion of a free-floating water-born target were demonstrated using a water propellant. Laser propulsion studies that used liquid propellant, such as [7,8], often exhibited a low specific impulse; however, at least one study [9] already demonstrated operation in a vacuum with exhaust velocities of 5 km=s by exhaust confinement and preheating of the propellant.…”
Section: Previous Laser Ablation Propulsion Tractor Beam Researchmentioning
confidence: 99%
“…One study of remote control by laser ablation propulsion was conducted by the Yabe group [7,8], which researched a bulk liquid propellant laser propulsion thruster, the metal-free water cannon. Remote torque production and tractor-beam-like propulsion of a free-floating water-born target were demonstrated using a water propellant.…”
Section: Previous Laser Ablation Propulsion Tractor Beam Researchmentioning
confidence: 99%